Comparando opções de canal de distribuição para pequenos empreendedores - Souza, Carlos Eduardo Margarido de (2019)
This paper compares distribution channels options for small entrepreneurs in São Paulo. The scope excludes on-line retail services, privately owned stores, and resellers; focusing on alternatives which operate as a service for this public, and are common throughout the city, such as open markets and collaborative shops.It is suggested a comparative framework between the two options, via the service marketing mix, adapted to the realities of the industry. With the goal of discovering and evaluating which attributes compose the small entrepreneurs comparison, and how they view each option. Those objectives are met throught a qualitative research, conducted with 21 owners and partners of small-scaled companies engaged in both distribution channels. Respondents arev prompted to enlist criteria used to differentiate and rank both propositions, spountaneously and conducted. It corroborates its propositions, concluding small entrepreneurs classify collaborative shops more favorably, are able to tell open markets apart from collaborative shops, and adopt a wide qualification approach, not concerning only with bottom line results. The research posts contributions for the academy and the market. It centers around a group of entrepreneurs frequently exposed to analytical myopias, because of their limited scale and scope. And contributes insights about the decision process of choice appreciation in distribuition channels, made in such a small conjecture.